Rice husk substrates and pruning time for gypsophila production - Höhn, Daniela; Nogueira Peil, Roberta Marins; Perin, Lais; Marchi, Priscila Monalisa; Grolli, Paulo Roberto; Radtke Wieth, Albertina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 475-483).